INFORMÁCIA A INFORMAČNÁ STRATÉGIA V DOPRAVNEJ FIRME (Perner's Contacts, 2007)
The informatisation of society connects to terms like data, information, knowledge and wisdom. As the transport companies are establishing on the market these terms are from time to time revalued. The aim of this article is to implement a new scientific knowledge into practice.
Keywords: informatisation; information strategy; transportation